A Successfully Treated Case of Recurrent Focal Segmental Glomerulosclerosis (FSGS) with Plasmapheresis and High dose Methylprednisolone Pulse Therapy - Sun Mi Her; Keum Hwa Lee; Jae Il Shin (Korean Society of Pediatric Nephrology, 2017)
Focal segmental glomerulosclerosis (FSGS) in children, which is a kind of nephrotic syndrome showing steroid resistance, usually progresses to a substantial number of end stage renal disease (ESRD). Although the pathogenesis of primary FSGS is unclear, several recent studies have reported that FSGS is associated with circulating immune factors such as soluble urokinase-type plasminogen activator receptor (suPAR) or anti-CD40 autoantibody. We report a successfully treated case of a 19-year-old female patient who experienced a recurrence of primary FSGS. After the diagnosis of FSGS, the patient progressed to ESRD and received a kidney transplantation (KT). Three days later, recurrence was suspected through proteinuria and hypoalbuminemia. She has been performed plasmapheresis and high dose methylprednisolone pulse therapy and shown remission status without increasing proteinuria for four years after KT. In conclusion, strong immunosuppressive therapy may be helpful for a good prognosis of recurrent FSGS, suppressing several immunologic circulating factors related disease pathogenesis.